IDENTIFIKASI PEMANGKU KEPENTINGAN DAN PERANAN DALAM PENGELOLAAN HUTAN LINDUNG GUNUNG SIRIMAU, KOTA AMBON, PROVINSI MALUKU - Evelin Parera; Ris Hadi Purwanto; Dwiko Budi Permadi; Sumardi Sumardi (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
Protected forest management is the responsibility of all stakeholders related to it. This study aims to identify stakeholders and their roles in protected forest management. The research was conducted in the Mount Sirimau Protection Forest Group, Maluku Province. Collecting data using questionnaires, in-depth interviews, observation and secondary data. Purposive sampling for agencies that have the main tasks and functions and the snow ball method for other stakeholders involved in protected forest management. Data analysis is descriptive qualitative. The results of the identification found the Technical Implementation Unit of the Ambon Island Forest Management Unit and the Lease Islands. Management of protected forests on Ambon Island is intervened by agencies and Technical Implementing Units within the scope of Forestry according to their main duties and functions. Other contributing stakeholders such as Community Social Institutions, Community Organizations, Religious Organizations, Academics, Agencies outside the scope of Forestry such as Public Works and People's Settlements in the Spatial Sector. The role of stakeholders as managers, intervenors, facilitators, participants, evaluators, expert teams, forest resource users and spatial planners.